Conserved-residue mutations in Wzy affect O-antigen polymerization and Wzz-mediated chain-length regulation in Pseudomonas aeruginosa PAO1 - Islam, Salim T. (Nature Publishing Group, 2013)
O antigen (O-Ag) in many bacteria is synthesized via the Wzx/Wzy-dependent pathway in which Wzy polymerizes lipid-linked O-Ag subunits to modal lengths regulated by Wzz. Characterization of 83 site-directed mutants of Wzy from Pseudomonas aeruginosa PAO1 (Wzy(Pa)) in topologically-mapped periplasmic (PL) and cytoplasmic loops (CL) verified the functional importance of PL3 and PL5, with the former shown to require overall cationic properties. Essential Arg residues in the RX(10)G motifs of PL3 and PL5 were found to be conserved in putative homologues of Wzy(Pa), as was the overall sequence homology between these two periplasmic loops in each protein. Amino acid substitutions in CL6 were found to alter Wzz-mediated O-antigen modality, with evidence suggesting that these changes may perturb the C-terminal Wzy(Pa) tertiary structure. Together, these data suggest that the catch-and-release mechanism of O-Ag polymerization is widespread among bacteria and that regulation of polymer length is affected by interaction of Wzz with Wzy.